Characterization of a Novel Nutrition and Traumatic Brain Injury Data Repository for the U.S. Armed Forces and Beneficiaries, 2017 to 2024 - Katrina S Monti; Zachary T Colburn; Michael T Fredericks; William R Conkright (Military Medicine, 2026)
ABSTRACT Introduction Traumatic brain injury (TBI) is a significant U.S. military health concern. Although emerging evidence suggests that nutrition may contribute to TBI outcomes, research on clinical nutrition interventions, especially within military populations, is limited because of a lack of data repositories that integrate the Nutrition Care Process, lifestyle factors, and clinical outcomes. Materials and Methods We established a novel Nutrition and TBI Data Repository, integrating TBI and nutrition care data from military health records spanning from January 1, 2017, to December 31, 2024. Our data repository leverages 12 distinct data sources and includes clinical encounter, laboratory, radiology, and pharmacy data, among others. Results Our repository contains clinical data for 431,673 patients with TBI and a 1:1 age- and sex-matched control cohort. The patient population is predominantly male (56.2%) and aged 17-41 years (39.5%). Most first-recorded TBIs are classified as mild (72.5%), and for 67.0% of the TBI cohort, mild represents the highest recorded severity. Active component service members make up 19.8% (n = 170,888) of the repository. We report patient counts across 23 health condition categories: 9 chronic health, 4 nutrition-related, 4 lifestyle factors, 3 sleep disorders, and 4 mental health disorders and 10 procedural code categories, including nutrition procedural codes. Overall, the TBI cohort has higher rates of health conditions, lifestyle codes, and nutrition counseling than controls. Conclusions Our Nutrition and TBI Data Repository is the first of its kind, integrating longitudinal patient-level nutrition care data with TBI outcomes sourced directly from the Military Health System to enable researchers to identify critical knowledge gaps in TBI and nutrition care and explore the role of nutrition in TBI recovery.